Historical institutionalism, political settlement and land ownership system in Nigeria - Yuhao Tan (International Journal of Urban Sustainable Development)
This study examines the evolution of land ownership in Nigeria through the lens of historical institutionalism and political settlements, analysing how the distribution of political power – both vertical and horizontal – has shaped institutional change. Using systematic process analysis (SPA), the research traces the persistence of institutional layering in land governance from pre-colonial times to the present day. The findings reveal that efforts to displace pre-existing tenure systems, particularly during the colonial and post-independence periods, were undermined by weak state enforcement capacity, resulting in a fragmented land tenure system where statutory, customary, and Islamic frameworks persist in legal and administrative tension. The study further highlights how land grabbing, political instability, and clientelist networks have deepened governance challenges, reinforcing legal pluralism and obstructing reform. These findings demonstrate that land reform failures in Nigeria stem not only from legal ambiguities but also from entrenched political settlements that sustain institutional fragmentation.